How to Add and Subtract Rational Expressions

By knowing a few simple rules you can easily add and subtract Rational Expressions. In this blog post, we will introduce you step by step guide on how to add and subtract rational expressions.

A step-by-step guide to Adding and Subtracting Rational Expressions

For adding and subtracting rational expressions:

• Find the least common denominator (LCD).
• Write each expression using the LCD.
• Add or subtract the numerators.
• Simplify as needed

Examples

Adding and Subtracting Rational Expressions – Example 1:

Solve: $$\frac{4}{2x+3}+\frac{x-2 }{2x+3}=$$

Solution:

The denominators are equal. Then, use fractions addition rule: $$\frac{a}{c}±\frac{b}{c}=\frac{a ± b}{c}→\frac{4}{2x+3}+\frac{x-2}{2x+3}=\frac{4+(x-2) }{2x+3}=\frac{x+2}{2x+3}$$

Adding and Subtracting Rational Expressions – Example 2:

Solve $$\frac{x + 4}{x – 5}+\frac{x – 4}{x + 6}$$=

Solution:

Find the least common denominator of$$(x-5)$$ and $$(x+6): (x-5)(x+6)$$
Then: $$\frac{x + 4}{x – 5}+\frac{x – 4}{x + 6}=\frac{(x+4)(x+6)}{(x-5)(x+6)}+\frac{(x – 4)(x-5)}{(x + 6)(x-5)}=\frac{(x+4)(x+6)+(x – 4)(x-5)}{(x + 6)(x-5)}$$
Expand: $$(x+4)(x+6)+(x-4)(x-5)=2x^2+x+44$$
Then: $$\frac{(x+4)(x+6)+(x – 4)(x-5)}{(x + 6)(x-5)}=\frac{2x^2+x+44}{(x +6)(x-5)}=\frac{2x^2+x+44}{x^2+x-30}$$

Adding and Subtracting Rational Expressions – Example 3:

Solve: $$\frac{3}{x+4}+\frac{x-2 }{x+4}$$=

Solution:

Use fraction addition rule: $$\frac{a}{c}±\frac{b}{c}=\frac{a ± b}{c}→\frac{3}{x+4}+\frac{x-2}{x+4}=\frac{3+(x-2) }{x+4}=\frac{x+1}{x+4}$$

Adding and Subtracting Rational Expressions – Example 4:

Solve: $$\frac{x + 4}{x – 8}+ \frac{x }{x + 6}$$=

Solution:

Least common denominator of $$(x-8)$$ and $$(x+6): (x-8)(x+6)$$
Then: $$\frac{(x+4)(x+6)}{(x-8)(x+6)}+\frac{x(x-8)}{(x + 6)(x-8)}=\frac{(x+4)(x+6)+x(x-8)}{(x + 6)(x-6)}$$
Expand: $$(x+4)(x+6)+x(x-8)=2x^2+2x+24$$
Then: $$\frac{x + 4}{x – 8}+ \frac{x }{x + 6}=\frac{2x^2+2x+24}{(x +6)(x-8)}$$

Exercises for Simplifying Fractions

1. $$\color{blue}{\frac{3}{x+1}-\frac{4x}{x+1}=}$$
2. $$\color{blue}{\frac{x+8}{x+1}+\frac{x-9}{x+2}=}$$
3. $$\color{blue}{\frac{6x}{x+5}+\frac{x+2}{x+7}=}$$
4. $$\color{blue}{\frac{15}{x+6}-\frac{x+1}{x^{2}-36}=}$$
5. $$\color{blue}{\frac{x+4}{x+3}-\frac{5x}{x-3}=}$$
6. $$\color{blue}{\frac{x+8}{x-4}+\frac{x-5}{x^{2}-16}=}$$
1. $$\color{blue}{\frac{3-4x}{x+1}}$$
2. $$\color{blue}{\frac{2x^2+2x+7}{(x+1)(x+2)}}$$
3. $$\color{blue}{\frac{7x^2+49x+10}{(x+5)(x+7)}}$$
4. $$\color{blue}{\frac{14x-91}{(x+6)(x-6)}}$$
5. $$\color{blue}{\frac{-4x^2-14x-12}{(x+3)(x-3)}}$$
6. $$\color{blue}{\frac{x^2+13x+27}{(x+4)(x-4)}}$$

36% OFF

X

How Does It Work?

1. Find eBooks

Locate the eBook you wish to purchase by searching for the test or title.

3. Checkout

Complete the quick and easy checkout process.

Save up to 70% compared to print

Help save the environment